2020
DOI: 10.3389/fimmu.2020.580968
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cells Mediate the Development of Liver Fibrosis in High Fat Diet-Induced NAFLD in Humanized Mice

Abstract: Non-alcoholic fatty liver disease (NAFLD) has been on a global rise. While animal models have rendered valuable insights to the pathogenesis of NAFLD, discrepancy with patient data still exists. Since non-alcoholic steatohepatitis (NASH) involves chronic inflammation, and CD4 + T cell infiltration of the liver is characteristic of NASH patients, we established and characterized a humanized mouse model to identify humanspecific immune response(s) associated with NAFLD progression. Immunodeficient mice engrafted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 46 publications
(101 reference statements)
8
63
1
Order By: Relevance
“…Similarly, 30,120 T cells were divided into seven subtypes, including natural killer T (NKT) cells (T1), CD4 + T cells (T2, T3, and T4), CD8 + T cells (T5 and T6), and specific Ramp1 + T cells (T7), with distinct transcriptomic signatures (Figure 4A-C). In particular, the number of subtypes T3 (CD4 + Foxp3 + regulatory T cells) and T6 (effector memory CD8 + T cells) was notably elevated in the HF-MCD group, which consistent with previous studies that activated CD4 + and CD8 + T cells is essential for the progression of NASH and liver fibrosis (Figure 4C) (14,36). T4 and T5 are naive CD4 + and CD8 + T cells with high expression of Ccr7 and Sell (10).…”
Section: Resultssupporting
confidence: 90%
“…Similarly, 30,120 T cells were divided into seven subtypes, including natural killer T (NKT) cells (T1), CD4 + T cells (T2, T3, and T4), CD8 + T cells (T5 and T6), and specific Ramp1 + T cells (T7), with distinct transcriptomic signatures (Figure 4A-C). In particular, the number of subtypes T3 (CD4 + Foxp3 + regulatory T cells) and T6 (effector memory CD8 + T cells) was notably elevated in the HF-MCD group, which consistent with previous studies that activated CD4 + and CD8 + T cells is essential for the progression of NASH and liver fibrosis (Figure 4C) (14,36). T4 and T5 are naive CD4 + and CD8 + T cells with high expression of Ccr7 and Sell (10).…”
Section: Resultssupporting
confidence: 90%
“…Humanized mouse models of dietinduced MAFLD showed a remarkable liver infiltration of CD4+, CD8+T cells and macrophages (CD68+), which were largely confined to fibrotic regions. Conversely, depletion of CD4+T cells abrogated diet-induced inflammatory response and liver fibrosis development (77). Further studies have shown that blocking integrin receptor a4b7-mediated recruitment of CD4+ T cells to the intestine and liver, not only attenuates hepatic inflammation and fibrosis, but also improves metabolic alterations associated with MAFLD (78).…”
Section: The Role Of the Immune System In The Pathogenesis Of Mafldmentioning
confidence: 99%
“…The use of IL-17A–deficient mice models has been shown to improve/resist to the development of steatohepatitis, a major risk factor of fibrosis ( 101 , 102 ). Humanized mice on high fat diet with induced NAFLD develop liver fibrosis that is mediated by CD4 + IL17A + cells ( 103 ). The depletion of CD4 + cells in these mice reduced fibrosis and inflammation but not steatosis.…”
Section: Il-17a Il-22 and Ra In Liver Fibrosismentioning
confidence: 99%